Comparison of outcomes between a single long stent and overlapping stents in long coronary artery lesion: a meta-analysis of the current literature. (3rd October 2022) - Saylik, F; Cinar, T; Selcuk, M; Cicek, V; Hayiroglu, M I; Orhan, A L
Abstract: Background: There is no consensus for the treatment of diffuse coronary artery lesions with a single long stent (SLS) or with overlapping of two or more stents (OLS). In this review, we aimed to compare the outcomes between these two approaches by performing a meta-analysis based on the literature. Methods: We searched MEDLINE, Scopus, EMBASE, Google Scholar, and the Cochrane Library for eligible studies. In total, 12 studies (n=6414) that included the outcomes in the follow-up period were included in this meta-analysis. Results: Patients with OLS had higher risk of cardiac death and target lesion revascularization (TLR) than those with SLS (RR: 1.51, confidence interval: 1.03–2.21, p=0.03, I 2 =0% and RR: 1.64, confidence interval: 1.02–2.65, p=0.04, I 2 =38%, respectively). Fluoroscopy time was prolonged in OLS group compared to SLS group (SMD: 0.35, confidence interval: 0.25–0.46, p<0.01, I 2 =0%). Contrast volume usage was higher in the OLS group, but there was significant heterogeneity in pooled analysis (I 2 =95%). In subgroup analysis, there were no differences with respect to outcomes between the studies reported before and after the year 2015. Conclusion: This was the first meta-analysis to indicate that cardiac death and TLR were higher and fluoroscopy time was longer in the OLS group than in the SLS group. Funding Acknowledgement: Type of funding sources: None.